2020
DOI: 10.1016/j.celrep.2020.108406
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Epigenetic Aging and Leukocyte Analysis of Simulated Space Travel: The Mars-500 Mission

Abstract: Highlights d Mission duration was associated with significant decreases in epigenetic aging d Decreases in PhenoAge, a morbidity biomarker, remained significant post-mission d There were significant changes in estimated proportions of some white blood cells d Only decreases in NK cells remained significant post-mission

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…The presence of sampling points before the isolation period could have enhanced our understanding of these personalized dynamics by setting up a “baseline microbiota” for each crewmember. Unfortunately, as for the other experiments done within Mars500 mission (see for instance [ 16 , 17 , 26 28 ]) due to the military nature of the Mars500 experiment, no sample of crewmembers before the mission was taken/made available, limiting our discussions to the isolation period itself. Other studies based on the Mars500 mission had the same experimental design but came to slightly different conclusions probably due to different human districts sampled.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of sampling points before the isolation period could have enhanced our understanding of these personalized dynamics by setting up a “baseline microbiota” for each crewmember. Unfortunately, as for the other experiments done within Mars500 mission (see for instance [ 16 , 17 , 26 28 ]) due to the military nature of the Mars500 experiment, no sample of crewmembers before the mission was taken/made available, limiting our discussions to the isolation period itself. Other studies based on the Mars500 mission had the same experimental design but came to slightly different conclusions probably due to different human districts sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, as for the other experiments done within Mars500 mission (see for instance [16,17,[26][27][28]) due to the military nature of the Mars500 experiment, no sample of crewmembers before the mission was taken/made available, limiting our discussions to the isolation period itself. Other studies based on the Mars500 mission had the same experimental design but came to slightly different conclusions probably due to different human districts sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Because telomere length is considered a marker of cellular aging, aging being usually associated with decreased telomere length 9 , 10 , the NASA twin study suggests a possible anti-aging effect of long-duration space travel. Another study on blood DNA methylation of six participants of the Mars-500 mission, a high-fidelity 520-day ground simulation experiment, showed that mission duration was associated with significant decreases in epigenetic aging at the 168- and 300-day time points 11 . DNA methylation, including DNAmPhenoAge, is a robust predictor of mortality risk that is also highly correlated with chronological age 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Another study on blood DNA methylation of six participants of the Mars-500 mission, a high-fidelity 520-day ground simulation experiment, showed that mission duration was associated with significant decreases in epigenetic aging at the 168- and 300-day time points 11 . DNA methylation, including DNAmPhenoAge, is a robust predictor of mortality risk that is also highly correlated with chronological age 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%